Patterns of Repertoire Conflict in Indonesia: A Study of #Indonesia Gelap News on Detik.com - Jati, Susilastuti Dwi Nugraha; Soeprapto, Adi; Wibawa, Arif (RSF Conference Series: Business, Management and Social Sciences, 2025)
The administration of Prabowo Subianto and Gibran Rakabuming Raka began amid protests initiated by the Indonesian Student Executive Board (BEM SI). This student movement presented nine demands to the government, covering economic, social, legal, and political issues. The movement, known as #IndonesiaGelap, utilized this theme to create tension and garner support from various segments of society, which in turn drew a response from the ruling authorities. This analysis examines Detik.com’s coverage of the #IndonesiaGelap student movement, utilizing Charles Tilly’s repertoire tension theory as the theoretical framework. The study applies Norman Fairclough’s critical discourse analysis, examining three elements: text, discourse practice, and social practice. The findings reveal that Detik.com consistently included #IndonesiaGelap in all its news headlines. Conflicting repertoires are reflected in the news texts, where students used the #IndonesiaGelap theme as a strategy to criticize government policies viewed as unsupportive of the people, thereby mobilizing support among university students. During the demonstrations, those in power also adopted the repertoire to present themselves as open to criticism. In conclusion, this study finds that the #IndonesiaGelap repertoire has limited effectiveness in promoting sociopolitical change, mainly due to the lack of social capital possessed by both the student movement and Detik.com within the existing power structure.